Work Stressors аnd Burnout Syndrome аmong Police Officers - Jaredić, Biljana N.; Radović, Olivera B. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
Research consistently highlights policing as one of the most challenging professions. The daily pressure faced by officers can have a significant impact on their psychophysical functioning. Various levels of risk threaten the safety of both police officers and the individuals they serve. From managing public events to responding to crimial activity, police officers are constantly tested in their ability to handle stress. Prolonged exposure to stressful situations can take a serious toll on their physical and emotional health, often hindering efforts to adopt healthy habits or maintain overall well-being. One of the most notable psychological effects of chronic stress is burnout syndrome, which represents the final stage in an officer’s attempt to adapt to the stressors they encounter.